Integration of Transcriptome and Methylome Highlights the Roles of Cell Cycle and Hippo Signaling Pathway in Flatfish Sexual Size Dimorphism - Wang, Na; Yang, Qian; Wang, Jialin; Shi, Rui; Li, Ming; Gao, Jin; Xu, Wenteng; Yang, Yingming; Chen, Yadong; Chen, Songlin (Frontiers in Cell and Developmental Biology, 2021)
Sexual size dimorphism (SSD) is the difference in segments or body size between sexes prevalent in various species. Understanding the genetic architecture of SSD has remained a significant challenge owing to the complexity of growth mechanisms and the sexual influences among species. The Chinese tongue sole (Cynoglossus semilaevis), which exhibits a female-biased SSD and female to male sex reversal, is an ideal model for exploring SSD mechanism at the molecular level. The present study aimed to integrate transcriptome and methylome analysis to unravel the genetic and epigenetic changes in female, male, and pseudomale C. semilaevis. The somatotropic and reproductive tissues (brain, liver, gonad, and muscle) transcriptomes were characterized by RNA-seq technology. Transcriptomic analysis unravelled numerous differentially expressed genes (DEGs) involved in cell growth and death-related pathways. The gonad and muscle methylomes were then employed for screening differentially methylated genes (DMGs). Relatively higher DNA methylation levels were observed in the male and pseudomale individuals. In detail, hypermethylation of the chromosome W was pronounced in the pseudomale group than in the females’ group. Furthermore, weighted gene co-expression network analyses showed that turquoise and brown modules positively and negatively correlated with the female-biased SSD, respectively. A combined analysis of the module genes and DMGs revealed the female-biased mRNA transcripts and hypomethylated levels in the upstream and downstream regions across the cell cycle-related genes. In addition, the male and pseudomale-biased gene expression in the hippo signaling pathway were positively correlated with their hypermethylation levels in the gene body. These findings implied that the activation of the cell cycle and the inhibition of the hippo signaling pathway were implicated in C. semilaevis female-biased SSD. In addition, the dynamic expression pattern of the epigenetic regulatory factors, including dnmt1, dnmt3a, dnmt3b, and uhrf1, among the different sexes correspond with their distinct DNA methylation levels. Herein, we provide valuable clues for understanding female-biased SSD in C. semilaevis.